Postsurgical Paracicatricial Cutaneous Satellitosis of Giant Cell Tumour of the Tendon Sheath, Localized Type - V. Caputo; S. Fiorella; E. Orlando (Karger Publishers, 2011)
Tenosynovial giant cell tumour (localized type) is a tumour of tendon sheaths and interphalangeal joints, affecting the digits and arising from the synovium. It is characterized by a proliferation of mononuclear cells and osteoclast-like polykaryocytes. Its propagation to the skin is an exceptional event, which can take place either in localized form in the fingertips (localized type) or in the rare diffuse form called giant cell tumour of the tendon sheath (diffuse type). We report here a case of giant cell tumour with cutaneous satellites, which appeared close to and around the surgical scar following the excision of the primary lesion, in a 9-year-old boy. In the cutaneous satellites, a few signs of transformation could be observed, consisting of the lack of stroma and pronounced cellularity characterized by sheets of rounded synovial-like cells admixed with multinucleated giant cells and xanthoma cells. No relapse was observed 1 year after a plastic surgery procedure (complete replacement of the involved skin). Diffuse lesions usually represent a diagnostic problem in comparison with their localized counterparts. The malignant transformation of an originally typical tenosynovial giant cell tumour is a rare but well-documented event. Our case seems to represent a typical example because the pronounced cellularity might wrongly lead to a diagnosis of malignancy.